A case report of acute intermittent porphyria leading to severe disability - Lin, Jie; Liu, Jinzhi; Wang, Aihua; Si, Zhihua (Frontiers in Neurology, 2024)
Acute intermittent porphyria (AIP) is a rare inherited metabolic disorder resulting from increased production of porphyrins and their precursors, δ-aminolevulinic acid (ALA) and porphobilinogen (PBG), due to deficiencies in the enzymatic activity of the heme synthesis pathway. The disease is typically characterized by a triad of abdominal pain, neurologic impairment symptoms, and psychiatric abnormalities. However, only a small percentage of patients present with this classic triad of symptoms. Our female patient, aged 23, was admitted to the hospital with a 4-year history of abnormal mood episodes and weakness in the limbs for over 1 week. She had a previous medical history of intestinal obstruction. After admission, a cranial MRI revealed reversible posterior leukoencephalopathy imaging manifestations, and the patient exhibited weakness of the extremities, respiratory failure, seizures, and severely reduced serum sodium concentration. The diagnosis of AIP was ultimately confirmed by a positive urine PBG-sunlight test and analysis of HMBS gene variants. The absence of typical triadic signs in acute attacks of AIP can make early recognition of the disease challenging. We present a case with multiple typical clinical manifestations of AIP in the hope of aiding clinicians in fully recognizing acute intermittent porphyria.